Monitoring of the microstructure of ion‐irradiated nuclear ceramics by in situ Raman spectroscopy. (14th December 2015) - Miro, S.; Bordas, E.; Thomé, L.; Costantini, J.‐M.; Leprêtre, F.; Trocellier, P.; Serruys, Y.; Beck, L.; Gosset, D.; Verlet, R.; Huguet‐Garcia, J.; Tupin, M.; et al.
Abstract : Raman spectroscopy is an efficient technique for studying the evolution of microstructure of materials under irradiation. For that purpose, a Raman spectrometer has been recently installed at the JANNUS‐Saclay platform. In this paper, we describe the new setup for in situ experiments. These in situ experiments allowed following the microstructural evolution of different materials (SiC, ZrO2 and B4 C) as a function of ion fluence on a single sample (either single crystal or polycrystalline ceramics) under the same irradiation conditions. Our results show that Raman spectroscopy is a versatile non‐contact technique for studying on‐line crystalline phase changes or amorphization of irradiated iono‐covalent solids. A detailed analysis of Raman spectra is provided for the three materials (SiC, ZrO2 and B4 C) investigated in this study, revealing quite different behaviors upon irradiation. Basically, Raman spectroscopy gives insight on these evolutions at the level of bonds given by specific phonon modes, in good agreement with Rutherford backscattering channeling (RBS/C), X‐ray diffraction (XRD) or transmission electron microscopy (TEM) data, which provide information at a long‐range scale. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : A Raman spectrometer has been recently coupled to the triple beam irradiation chamber of the JANNUS‐Saclay platform. These in situ experiments allowed following the microstructural evolution of materials as a function of ion fluence on a single sample under the same irradiation conditions. A detailed analysis of Raman spectra for different materials investigated (SiC, ZrO2 and B4 C) reveals quite different behaviors upon irradiation, such as phase change for ZrO2 or amorphization for SiC.